1989
DOI: 10.1210/jcem-68-1-173
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Hormonal Characteristics of Obese Amenorrheic Hyperandrogenic Women Before and After Weight Loss*

Abstract: We studied a group of obese hyperandrogenic amenorrheic women to determine the effects of weight loss on anthropometry, hormonal status, menstrual cycles, ovulation, and fertility. Fourteen women had polycystic ovaries, two the hyperandrogenism-insulin resistance-acanthosis nigricans syndrome, one hirsutism of adrenal origin, and three idiopathic chronic anovulation. The duration of amenorrhea before the study ranged from 3-17 months [mean, 8.6 +/- 4.5 (+/- SD)]. All women ate a hypocaloric diet for a period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
2
12

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(176 citation statements)
references
References 24 publications
9
153
2
12
Order By: Relevance
“…The current study, like previous ones [36][37][38] indicated that treatment with orlistat led to a significant reduction in testosterone concentration. Orlistat is a weight loss drug with minimal systemic absorption [24] and therefore any effect of this drug is a result of weight loss and not the direct effect on ovaries.…”
Section: Discussionsupporting
confidence: 88%
“…The current study, like previous ones [36][37][38] indicated that treatment with orlistat led to a significant reduction in testosterone concentration. Orlistat is a weight loss drug with minimal systemic absorption [24] and therefore any effect of this drug is a result of weight loss and not the direct effect on ovaries.…”
Section: Discussionsupporting
confidence: 88%
“…Short-term low calorie diets (4 weeks) with 6.6-9.0% weight loss have been shown to decrease IR (Hamilton-Fairley et al, 1993;Andersen et al, 1995). Studies of moderate caloric restriction for 2-15 months also gave positive outcomes (Pasquali et al, 1989). Encouragingly small reductions in weight (~5% body weight) have led to positive clinical improvements.…”
Section: Non-pharmacological Management Of Obesity In Pcos Patientsmentioning
confidence: 99%
“…13 Dietary intervention studies have demonstrated that weight loss via restricted energy intake results in improved clinical status in PCOS patients. 14,15 Weight loss in hyperandrogenic obese anovulatory women has been shown to result in a normalization of insulin sensitivity, 16,17 androgen levels, 15,[18][19][20] and SHBG level. 20,21 Long-term dietary interventions have also shown that weight loss in obese women with PCOS results in normalization of menstrual functioning and fertility.…”
Section: Introductionmentioning
confidence: 99%